New opportunities for biologically and chemically mediated adsorption and precipitation of phosphorus from wastewater - Pratt, Chris; Soares, Ana (Elsevier, 2025)
Biologically mediated adsorption and precipitation of phosphorus (P) from waste streams can restrict environmental P discharges. Here, we appraise progress in this field over the past decade. The research discipline has grown considerably in recent years. Industry ‘wastes’, including steel slags, continue to show promise as adsorbents with exceptionally high P retention capacities (>500 mg P g−1). Hydrotalcite, a nanomineral, offers prospects as a P removal technology with imbedded climate change mitigation capacity. Biomineral struvite formation, driven by microbial processes, offers an exciting P removal and recovery approach that can be applied to diverse wastewater types due to its feedstock-independent mechanisms, emerging immobilisation techniques and adaptability to mixed cultures. All of these factors facilitate efficient nutrient recycling and scalable application to the wastewater industry. Adsorbed and precipitated P can be applied to cropland to offset dependence on conventional fertiliser inputs. Therefore, in addition to water treatment, these biologically mediated processes also offer opportunities to support food production. Moreover, as many of the input materials covered in this review are industry byproducts and common organic materials, the removal of P from waste streams by adsorption and precipitation offers strong circularity potential that aligns with the UN's Sustainable Development Goals. We call for future work to focus on long-term full-scale trials involving community, government and industry partners.
Keywords: 30 Agricultural, Veterinary and Food Sciences; 31 Biological Sciences; 32 Biomedical and Clinical Sciences; 3106 Industrial Biotechnology; 3206 Medical Biotechnology; 3001 Agricultural Biotechnology; 12 Responsible Consumption and Production; Biotechnology; Phosphorus; Wastewater; Adsorption; Water Pollutants, Chemical; Water Purification; Chemical Precipitation